Prevalence of Surgical Site Infections Following Coronectomy: A Systematic Review and Meta-Analysis - Evangelos Kostares; Georgia Kostare; Michael Kostares; Athanasios Tsakris; Maria Kantzanou (Dentistry Journal)
Background/Objectives: This systematic review and meta-analysis aimed to investigate the prevalence of surgical site infections (SSIs) following coronectomy of mandibular third molars. Methods: A comprehensive literature search was conducted in Medline, Scopus, Web of Science, and Google Scholar databases up to 30 July 2024. Two independent reviewers performed study selection, data extraction, and quality assessment using the Newcastle–Ottawa Scale. Observational studies assessing SSI prevalence following coronectomy were included. The pooled prevalence of SSI with 95% confidence intervals (CI) was calculated using a random-effects model. Heterogeneity was assessed using the I2 statistic, and meta-regression was conducted to explore the influence of continuous variables. Results: A total of 22 studies involving 2173 coronectomy procedures were included. The overall pooled prevalence of SSI was 2.4% (95% CI: 1–4.3%), with substantial heterogeneity (I2 = 81%). Meta-regression showed no significant effect of the examined variables on SSI prevalence. No study was identified as a significant outlier. Quality assessments revealed that all studies had moderate methodological quality. Conclusions: Considerable heterogeneity was observed, likely due to variations in study settings, geographical regions, and timeframes, among other factors. Therefore, this study underscores the need for further rigorous research to better understand SSI risk factors and enhance management strategies for this postoperative complication.